G91 US National Perspective on Hospitalisations of Children with Pre-existing Tracheostomy. (7th April 2014) - Zhu, H; Das, P; Roberson, D; Skinner, M; Paine, M; Yuan, J; Berry, J
Abstract : Aims: (1) To describe the reasons, duration, and cost of hospitalisations in children with pre-existing tracheostomy, (2) to assess how many of these hospitalisations might be avoidable. Methods: This is a retrospective cohort analysis of the Healthcare Cost and Utilization Project Kids' Inpatient Database (KID) 2009. KID includes 3.4 million hospital discharges from 4, 121 hospitals in 44 states and has a weight variable for each observation so that weighted analyses may produce national estimates of total discharges in the United States for specific diagnoses and procedures. Children with tracheostomy were selected using ICD-9-CM tracheostomy diagnosis codes and we excluded hospitalisations where tracheostomy was performed. Length of stay, hospital costs and in-hospital mortality were compared in relation to the patients' demographic and clinical characteristics. Potentially avoidable hospitalisations (with improvements in outpatient and community care) were identified with ICD-9-CM codes for tracheostomy complications and ambulatory care sensitive conditions. Results: We identified 21, 429 hospitalisations of children with pre-existing tracheostomy, costing $1.42 billion (U.S.). Mean age at admission for children with tracheostomy was 6.6 years [standard deviation (SD) 6.5 years]. Patients had a mean of 5.1 (SD 2.3) chronic conditions and 67.1% (n = 14, 379) had a gastrostomy. Most hospitalisations were emergent (45.1%, n = 9663) or urgent (19.0%, n = 4079). Inpatient mortality was 1.6% (n = 352); 82.9% of patients (n = 17, 765) were discharged home and the remainder to another inpatient facility (15.5%, n = 3, 312). A respiratory problem was the most common reason for hospitalisation (50.4%, n = 10, 801) and the most common diagnoses were pneumonia (14.2%, n = 3051) and acute laryngitis or tracheitis (6.9%, n = 1475) (Table 1 ). Twenty-one percent (n = 4557) of all hospitalisations of children with tracheostomy were due to ambulatory care sensitive conditions; 40% (n = 1354) of these were due to dehydration and 36% (n = 1222) due to a tracheostomy complication (Table 2 ). Conclusions: This study gives the first ever national perspective that children with pre-existing tracheostomies are a complex group who experience costly hospitalisations and over half of these are primarily due to a respiratory diagnosis. Further investigation of hospitalisations for dehydration, tracheostomy complications and pneumonia, in particular, are necessary to assess how they may be avoided with improved co-ordination of multidisciplinary outpatient and community care.